Hubungan Faktor Lingkungan Fisik Perumahan dengan Kejadian Pneumonia pada Balita di Kota Padang: Studi Kasus : Wilayah Kerja Puskesmas Lubuk Bagalung - Rahma, Ragil (JURNAL RISET INOVASI DAERAH, 2025)
Pneumonia is one of the leading causes of death in children under five, especially in developing countries such as Indonesia. The physical environment of the household is believed to contribute to the increased risk of pneumonia. This study aims to analyze the relationship between housing physical environmental factors—including room ventilation area, natural lighting, room humidity, room occupancy density, and family smoking habits—and the incidence of pneumonia in children under five. This research employed a quantitative design with a cross-sectional approach. A total of 36 respondents were selected using purposive sampling in the working area of Lubuk Begalung Public Health Center, Padang City. Data were analyzed using univariate and bivariate analyses with the chi-square test. The results showed significant relationships between pneumonia incidence and natural lighting in the child’s room (p = 0.045), room humidity (p = 0.011), and indoor smoking by family members (p = 0.002). Meanwhile, ventilation area (p = 0.081) and room occupancy density (p = 0.715) were not significantly associated. In conclusion, lighting, room humidity, and indoor smoking habits are significantly associated with pneumonia incidence in children under five. Environmental interventions at the household level are necessary to reduce the risk of pneumonia, especially in vulnerable age groups.